YOUNG HABAIB: FROM SHOLAWAT ASSEMBLIES, DA’WA AND YOUNG PEOPLE'S RELIGIOUS EXPRESSION IN PONOROGO - Shella Syakhfiani Fatmarahadi Fatmarahadi; Riza Anggara Putra (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Abstract :This article seeks to explain the rise in popularity of a young habaib among young Muslims in Ponorogo, Habib Naqib bin Abdullah Assegaf, a young habaib with a sholawat Syubanul Shorot assembly that is widely idolised by young Muslims in Ponorogo. This study assumes that the young habaib relies more on entertainment performance than oratorical competence in attracting followers. The results of this study show that (1) Young Habaib have utilised new media and technology through the internet for self-promotion; (2) the promotional power possessed by the shalawat assembly is also supported by young people's congregation as the basis of da'wah and its market share which used to be filled by senior habaib (3) the practice of shalawat carried out by these young Habaib by combining the dimensions of spirituality and musicality so as to attract the attention of millennial youth in urban and rural areas. Keywords: Yuong Habib, Sholawat Assemblies, Religious Expression Abstrak: Artikel ini berusaha menjelaskan naiknya popularitas seorang habaib muda di kalangan anak muda Muslim di Ponorogo, Habib Naqib bin Abdullah Assegaf, seorang habaib muda dengan majelis sholawat Syubanul Shorot yang banyak diidolakan oleh anak muda Muslim di Ponorogo. Penelitian ini mengasumsikan bahwa habaib muda lebih mengandalkan pertunjukan hiburan daripada kompetensi oratoris dalam menarik pengikut. Hasil penelitian ini menunjukkan bahwa (1) Habaib muda telah memanfaatkan media baru dan teknologi melalui internet untuk promosi diri; (2) kekuatan promosi yang dimiliki majelis shalawat ini juga didukung oleh jamaah anak muda sebagai basis dakwah dan pangsa pasar yang dulunya diisi oleh para habaib senior; (3) pengamalan shalawat yang dilakukan para habaib muda ini dengan memadukan dimensi spiritualitas dan musikalitas sehingga mampu menarik perhatian kaum muda milenial di perkotaan dan pedesaan. Kata kunci: Habaib Muda, Majelis Sholawat, Ekspresi Keagamaan